2020
DOI: 10.1111/ejed.12414
|View full text |Cite
|
Sign up to set email alerts
|

Shadow education in the service of tiger parenting: Strategies used by middle‐class families in China

Abstract: Parents in many cultures invest significant proportions of household incomes in the so-called shadow education system of private supplementary tutoring. Parts of the literature attribute intensive tutoring to East Asian cultural traditions and to so-called tiger parenting. Based on a mixed-methods study in Shanghai, this article examines tiger parenting through a socio-economic lens to show the roles of shadow education in achieving parental goals. The study shows that

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(36 citation statements)
references
References 43 publications
2
33
0
1
Order By: Relevance
“…Participation in tutoring for children from highest-income families was also relatively low because it was “easier for the highest stratum to achieve school choice through other channels even if the children performed poorly, so these families were less likely to consider tutoring essential” (p. 395). Zhang’s (2020) research supports the model of subjective rationalities presented in this paper by highlighting the varied effects of different family cultural capital on parental approaches to tutoring in CHCs.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Participation in tutoring for children from highest-income families was also relatively low because it was “easier for the highest stratum to achieve school choice through other channels even if the children performed poorly, so these families were less likely to consider tutoring essential” (p. 395). Zhang’s (2020) research supports the model of subjective rationalities presented in this paper by highlighting the varied effects of different family cultural capital on parental approaches to tutoring in CHCs.…”
Section: Discussionsupporting
confidence: 78%
“…It is important to add that attitudes associated with CHCs are not equally widespread across social classes with different compositions of capital. Zhang (2020) concludes from an empirical research in Shanghai that the demand for tutoring was least among low-income families due to high costs and low aspirations. Participation in tutoring for children from highest-income families was also relatively low because it was “easier for the highest stratum to achieve school choice through other channels even if the children performed poorly, so these families were less likely to consider tutoring essential” (p. 395).…”
Section: Discussionmentioning
confidence: 99%
“…Research has found that parents with better socioeconomic resources are more likely to involve their children in the education market and participate in educational consumerism (Zhang, 2020). However, little study has focused on the way in which parents perform this classed parenting practice in the early years in contemporary Chinese society.…”
Section: Parenting and The Marketisation Of Educationmentioning
confidence: 99%
“…According to Zhang (2020), parents in contemporary Chinese society inherit traditions based on their social positions and practical needs. For example, the legacy of the ancient meritocratic education system, which was effectively used for the selection of the social elite, is still evident today.…”
Section: Cultural Model Of Chinese Parentingmentioning
confidence: 99%
See 1 more Smart Citation